How Capsule Wardrobe Discourse on Social Media Feminizes Minimalism and Aestheticizes Self-Restraint - Zhang, Min (Art and Society, 2025)
This paper critically examines the cultural phenomenon of capsule wardrobe discourse on social media, arguing that it feminizes minimalist aesthetics and aestheticizes self-restraint within a neoliberal framework. Drawing from feminist media theory, Foucault’s concept of governmentality, and critiques of digital consumer culture, the essay explores how capsule wardrobes serve not only as a fashion strategy but also as a symbolic system of aesthetic, emotional, and ethical labor. The analysis reveals how self-restraint is rebranded as empowerment, how unpaid curatorial labor is romanticized as feminine virtue, and how digital platforms reward visual coherence as a proxy for moral character. Capsule wardrobe influencers are shown to embody the ideal neoliberal subject—self-regulating, optimized, and perpetually productive—while simultaneously erasing the classed, racialized, and gendered dimensions of this aesthetic labor. The paper argues that the seemingly apolitical act of reducing one’s wardrobe functions as a performative ethic of aestheticized austerity, entrenching broader ideologies of digital femininity, self-branding, and consumer virtue under the veil of simplicity and style.